Fate of antibiotics in engineered wastewater systems and receiving water environment: A case study on the coast of Hangzhou Bay, China - Yingyu Bao; Feifei Li; Lyujun Chen; Mu, Qinglin; Huang, Bei; Wen, Donghui (Science of the Total Environment, 2021)
The occurrence of man-made antibiotics in natural environment has aroused attentions from both scientists and publics. However, few studies tracked antibiotics from their production site to the end of disposal environment. Taking the coastal region of Hangzhou Bay as the study area, the fate of 77 antibiotics from 6 categories in two-step wastewater treatment plants (WTPs, i.e. pharmaceutical WTP and integrated WTP) was focused; and the antibiotics in both dissolved and adsorbed phases were investigated simultaneously in this study. The ubiquitous occurrence of antibiotics was observed in the two-step WTPs, with antibiotic concentrations following the order of PWTP (LOQ - 1.0 × 105 ng·L−1) > IWTPi (for <a class="topic-link" href="https://www.sciencedirect.com/topics/earth-and-planetary-sciences/industrial-wastewater-treatment" title="Learn more about industrial wastewater treatment from ScienceDirect's AI-generated Topic Pages">industrial wastewater treatment, LOQ - 3.7 × 103 ng·L−1) > IWTPd (for domestic sewage treatment, LOQ - 1.3 × 103 ng·L−1). And the types of antibiotics detected in excess sludge and suspended particles were in accordance with those in wastewater. Quinolones were invariably dominant in both dissolved and adsorbed fractions. High removal efficiencies (median values >50.0%) were acquired for the dissolved quinolones (except for DFX), tetracyclines, β-lactams, and lincosamides. Anaerobic/anoxic/oxic achieved the highest aqueous removal of antibiotics among the investigated treatment technologies in the three WTPs. PWTP and IWTP removed 9797 and 487 g·d−1 of antibiotics, respectively; and a final effluent with 126.4 g·d−1 of antibiotics was discharged into the effluent-receiving area (ERA) of Hangzhou Bay. Source apportionment analysis demonstrated that the effluents of IWTPd and IWTPd contributed respectively 39.3% and 8.9% to the total antibiotics in the ERA. The results illustrate quantitatively the antibiotic flows from engineered wastewater systems to natural water environment, on the basis of which the improvements of wastewater treatment technologies and discharge management would be put forward.